Characterizing crystalline defects in single Xe nanoparticles from angular correlations of single-shot diffracted X-rays. Issue 20 (January 2020) - Niozu, A; Kumagai, Y; Nishiyama, T; Fukuzawa, H; Motomura, K; Bucher, M; Ito, Y; Takanashi, T; Asa, K; Sato, Y; You, D; Li, Y; et al.
Synopsis: We performed a wide-angle X-ray scattering experiment of single Xe nanoparticles using an X-ray free electron laser. We developed a novel analysis method that focuses on the angular correlation between plural Bragg spots in single-shot diffraction patterns. The angular correlations of the Bragg spots encode rich structural information and offer an evidence of twinning and stacking faults in Xe nanoparticles.